Values Education through the Exemplary of Sultan Syarif Kasim II for Students in Riau (History Department, Semarang State University and Historian Society of Indonesia, 2022)
Education of values through the example of a figure who is also a national hero from Riau is still lacking. It is necessary to have values education based on historical figures so that students cannot forget their heroes and imitate Sultan Syarif Kasim II’s struggles. This research was conducted using a qualitative method with a descriptive-analytical approach. The values reconstructed from the results of field research and literature studies are then integrated into the historical student learning at the University of Riau so that it is internalized into students who will later become self-character based on the fighting spirit of the heroes of Riau. Pendidikan nilai melalui keteladanan sosok yang juga merupakan pahlawan nasional asal Riau masih sangat kurang. Perlu adanya pendidikan nilai berbasis tokoh sejarah agar mahasiswa tidak melupakan pahlawannya sehingga mampu meneladani perjuangan yang telah dilakukan Sultan Syarif Kasim II. Penelitian ini dilakukan dengan menggunakan metode kualitatif dengan pendekatan deskriptif-analitis. Nilai-nilai yang telah direkonstruksi dari hasil penelitian lapangan dan studi literatur tersebut kemudian diintegrasikan ke dalam perkuliahan sejarah lokal mahasiswa sejarah Universitas Riau. Sehingga terinternalisasi ke dalam diri mahasiswa yang nantinya menjadi karakter diri yang dilandasi semangat perjuangan para pahlawan Riau. Cite this article: Pernantah, P.S., Ahmal. (2022). Values Education through the Exemplary of Sultan Syarif Kasim II for Students in Riau. Paramita: Historical Studies Journal, 32(2), 276-285. http://dx.doi.org/10.15294/paramita.v32i2.27632